Global Financial market tribulations-upshots on major Banks costs and profits - A Mauritian perspective - Polodoo, Viren; Padachi, Kesseven; Seetah, K. (IJMBS, 2013)
This paper appraises the upshots on Mauritian Banks following recent tribulations in global financial markets using data for the period 2000-2011. Using data from Banks' annual reports, a sample of 9 banks that existed during this period is taken to investigate the impact of recent tribulations in global financial markets on the costs and profits of the banks. Plain OLS results suggest that financial crisis has had no impact on the performance of the domestic banking sector as shown by the insignificance of the financial dummy variable. To have a more efficient and reliable estimate, the model has been tested using GMM. The GMM results also confirm the insignificance of the financial crisis dummy, which indicates that the Mauritian banking sector is very resilient to external economic and financial shocks